2020
DOI: 10.1186/s12877-020-01735-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of older adults with a persistent death wish without severe illness: a large cross-sectional survey

Abstract: Background Some older persons develop a persistent death wish without being severely ill, often referred to as “completed life” or “tiredness of life”. In the Netherlands and Belgium, the question whether these persons should have legal options for euthanasia or physician-assisted suicide (EAS) is intensely debated. Our main aim was to investigate the prevalence and characteristics of older adults with a persistent death wish without severe illness, as the lack of this knowledge is a crucial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Although most people would suffer from similar conditions more or less, presumably a majority would treat it more lightly and not develop a wish to die. The same goes for fears: most participants were horrified by all kinds of anticipated fears regarding the future, including but not limited to (further) development of certain illnesses, unwanted side-effects of possible treatment options, total dependence on others, and forced relocation (van Wijngaarden et al, 2015;van Wijngaarden et al, 2016;Hartog et al, 2020). Most people in a somewhat similar situation will recognise the concerns, but supposedly not become paralysed by such concerns and rather find ways to cope with them.…”
Section: Witnessing All Stories?mentioning
confidence: 99%
See 3 more Smart Citations
“…Although most people would suffer from similar conditions more or less, presumably a majority would treat it more lightly and not develop a wish to die. The same goes for fears: most participants were horrified by all kinds of anticipated fears regarding the future, including but not limited to (further) development of certain illnesses, unwanted side-effects of possible treatment options, total dependence on others, and forced relocation (van Wijngaarden et al, 2015;van Wijngaarden et al, 2016;Hartog et al, 2020). Most people in a somewhat similar situation will recognise the concerns, but supposedly not become paralysed by such concerns and rather find ways to cope with them.…”
Section: Witnessing All Stories?mentioning
confidence: 99%
“…What does it mean to live with a deep sense that life is no longer worth living? Over the years, I have conducted several studies in which I explored the lifeworld of people like Michael (van Wijngaarden et al, 2015;van Wijngaarden et al, 2016;Hartog et al, 2020). Analysing these stories brought into view several central meanings.…”
Section: Lived Experience Of Older Adults Suffering From Lifementioning
confidence: 99%
See 2 more Smart Citations
“…With regard to their age, 2.2% of 65-year-old Dutch persons may have had a wish to die (Rurup et al 2011), while another study among the European general population demonstrated that passive death wishes increases with age (of those 50-65 years of age, 5% have a passive death wish) (Ayalon and Shiovitz-Ezra 2011). Nonetheless, recently, a study among a representative sample of Dutch citizens aged 55 years and older (n ¼ 32,477), demonstrated no significant overall difference in age distribution between those having a persistent death wish without severe illness (n ¼ 267, 1.25%) and those without (Hartog et al 2020). As such, an ongoing debate in The Netherlands remains centered around the question of whether the Dutch government should allow legal support for selfdetermination, that is increased patient autonomy within the Euthanasia Act and its practice.…”
mentioning
confidence: 99%